The Effect of Vocabulary Instruction on Depth of Vocabulary Knowledge and Reading Comprehension Performance - Abdul Rahman, Rafiah (2008)
The study investigates the effect of vocabulary instruction on the depth of vocabulary knowledge and reading comprehension performance of English as Second Language (ESL) learners. It seeks to find out if teaching vocabulary contributes to the development of depth of vocabulary knowledge and reading comprehension performance. The experiment was carried out on 60 student teachers from one of the teachers’ training institutes in Malaysia. This study was a true experimental, employing the Solomon Four-Group design. The reading section of MUET and the Word Association Test (WAT) were used as the instruments. The reading test was scored using percentages. Further, it was analysed under the five levels of questions in Barrett's taxonomy of cognitive and affective difficulty of questions. The WAT was scored using percentages and was further analysed under the three semantic relationships: paradigmatic, syntagmatic and analytic. The statistical tests employed were the t-tests and the analysis ANOVA. Results indicate that vocabulary instruction has a significant difference on the participants’ reading comprehension performance. Further analysis indicates that there are significant differences only in the literal and reorganization level. The results also indicate that there is a significant difference on the subjects’ depth of vocabulary knowledge. Further analysis indicates that only the paradigmatic relationships are statistically significant. The findings support the interactive model of reading which recognizes the importance of vocabulary in the reading process. It also supports the linguistic threshold hypothesis (Clarke, 1979), which asserts that L2 reading ability depends on L2 language proficiency. The results also support the instrumentalist view (Anderson & Freebody, 1981), which claims that vocabulary knowledge is a direct factor in the causal chain resulting in reading comprehension. It can be concluded that vocabulary need to be taught explicitly to ESL learners in Malaysia in order for them to reach the vocabulary threshold level. The findings are discussed in relation to its pedagogical implications.